ASUHAN KEBIDANAN TERHADAP NY A USIA 20 TAHUN P1A0 2 JAM POSTPARTUM DENGAN PENATALAKSANAAN PERAWATAN LUKA PERINEUM DI PMB MARIA DWI SAPTA, S.ST BANDAR LAMPUNG - Mustika Oktaviani; Margareta Rinjani; Utama Ladunni Lubis; Dita Selvia Aditia (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2021)
Background: The incidence of perineal injuries in Asia is quite high, around 50% of the incidence of perineal tears (Bascom, 2011). received perineal sutures (28% due to episiotomy and 29% due to spontaneous tears) and 52% of mothers experienced perineal injuries due to delivery with babies with sufficient birth weight or more (MOH, 2016). Purpose: To apply Midwifery Care to NY A 20 Years Old P1A0 Postpartum with Perineal Wound Care Management at PMB Maria Dwi Sapta,S.ST. Bandar Lampung in 2021. Methods: This research is descriptive. Comprehensive care for Mrs. A 2 hours postpartum to 8 days and perineal wound care management. The treatment given is by performing perineal wound care and consuming 3-5 boiled eggs for the perineal wound healing process quickly and well. With the results on visits 1 and 2 the mother still experienced pain and the wound was not dry and on the third visit the wound on the mother's perineum had begun to close and dry so that the perineal wound that she experienced could be resolved. Result: p value obtained in the independent t test analysis test was obtained p-value = 0.000 which means that there is an effect of boiled egg consumption on perineal wound healing in postpartum mothers 1-7 days. Suggestion: it is expected that in providing information/knowledge can be understood and sustained with complaints felt by patients who can support care during the puerperium related to the management of perineal wound care.